METAPLASTIC CARCINOMA OF THE BREAST: A RARE TUMOUR - Cihangir Akyol; Atıl Çakmak; İlknur Kepenekçi; Ozan Şen; Seher Demirer (European Journal of Breast Health, 2008)

(untitled)
Metaplastic carcinoma of the breast (MCB) is a rare type of breast cancer accounting for < 1% of breast malignancies. The term metaplastic carcinoma was fi rst introduced by Huvos et al. MCB is an aggressive disease and has poor prognosis. MCB denotes a heterogeneous group of uncommon malignant entities. Conventionally the term is used to denote tumours with mixed malignant epithelial and malignant mesenchymal components. We report a case of MCB in 51 years old women. She has presented with palpable and progresivvely enlarging mass in the right breast. Modifi ed radical mastectomy was perfomed. Histopathologic diagnosis was reported as T2N1bııı, Grade III, ER (-), PR (-), cerbB2 (-) metaplastic breast carcinoma. Adjuvant chemotheraphy was performed. Recurrence has not been detected at 22 months after surgery.